On the Invariance of Demand for Cash and other Assets - Clower, R. W.; Burstein, M. L. (Review of Economic Studies, 1960)
Journal Article A Symposium on Monetary Theory: On the Invariance of Demand for Cash and other Assets Get access R. W. Clower, R. W. Clower Northwestern Search for other works by this author on: Oxford Academic Google Scholar M. L. Burstein M. L. Burstein Northwestern Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 1, October 1960, Pages 32–36, https://doi.org/10.2307/2296247 Published: 01 October 1960